Expert Recommendations on the Evaluation of Sunscreen Efficacy and the Beneficial Role of Non-filtering Ingredients - González, Salvador; Aguilera, José; Berman, Brian; Calzavara-Pinton, Piergiacomo; Gilaberte, Yolanda; Goh, Chee-Leok; Lim, Henry W.; Schalka, Sergio; Stengel, Fernando; Wolf, Peter; Xiang, Flora (Frontiers in Medicine, 2022)
A variety of non-filtering agents have been introduced to enhance sunscreen photoprotection. Most of those agents have only weak erythema protective properties but may be valuable and beneficial in supporting protection against other effects of UV radiation, such as photoimmunosuppression, skin aging, and carcinogenesis, as well as photodermatoses. The question arises how to measure and evaluate this efficacy since standard SPF testing is not appropriate. In this perspective, we aim to provide a position statement regarding the actual value of SPF and UVA-PF to measure photoprotection. We argue whether new or additional parameters and scales can be used to better indicate the protection conferred by these products against the detrimental effects of natural/artificial, UV/visible light beyond sunburn, including DNA damage, photoimmunosuppression and pigmentation, and the potential benefits of the addition of other ingredients beyond traditional inorganic and organic filters to existing sunscreens. Also, we debate the overall usefulness of adding novel parameters that measure photoprotection to reach two tiers of users, that is, the general public and the medical community; and how this can be communicated to convey the presence of additional beneficial effects deriving from non-filtering agents, e.g., biological extracts. Finally, we provide a perspective on new challenges stemming from environmental factors, focusing on the role of the skin microbiome and the role of air pollutants and resulting needs for photoprotection.